2013
DOI: 10.1101/gr.154070.112
|View full text |Cite
|
Sign up to set email alerts
|

Targeted chromosomal deletions and inversions in zebrafish

Abstract: Zinc finger nucleases (ZFNs) and transcription activator-like effector nucleases (TALENs) provide powerful platforms for genome editing in plants and animals. Typically, a single nuclease is sufficient to disrupt the function of protein-coding genes through the introduction of microdeletions or insertions that cause frameshifts within an early coding exon. However, interrogating the function of cis-regulatory modules or noncoding RNAs in many instances requires the excision of this element from the genome. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
64
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(69 citation statements)
references
References 42 publications
3
64
0
1
Order By: Relevance
“…Importantly, engineered chromosomally stable clones could be obtained using a standard subcloning and PCR screening procedure. Large deletions up to 24 megabases have been reported using zinc finger nucleases (Lee et al 2010(Lee et al , 2012 or TALENs (Gupta et al 2013;Kim et al 2013;Xiao et al 2013), but the efficiency cannot always be inferred because few studies reported the isolation of single clones carrying these deletions. In cases when single clones were isolated, they were retrieved at a surprisingly high frequency (;0.5%) , given the fact that TALENs are generally believed to be less efficient than the CRISPR/Cas9 system.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, engineered chromosomally stable clones could be obtained using a standard subcloning and PCR screening procedure. Large deletions up to 24 megabases have been reported using zinc finger nucleases (Lee et al 2010(Lee et al , 2012 or TALENs (Gupta et al 2013;Kim et al 2013;Xiao et al 2013), but the efficiency cannot always be inferred because few studies reported the isolation of single clones carrying these deletions. In cases when single clones were isolated, they were retrieved at a surprisingly high frequency (;0.5%) , given the fact that TALENs are generally believed to be less efficient than the CRISPR/Cas9 system.…”
Section: Discussionmentioning
confidence: 99%
“…47,48,58 Introduction of 2 engineered nucleases can result in targeted deletion or inversion, duplication, local indels at nuclease cleavage sites, or translocations/ chromosomal rearrangements. [60][61][62][63][64][65][66][67][68][69][70][71][72][73] Here, we review genome-editing approaches for genetic correction and disruption strategies for the b-hemoglobinopathies as summarized in Figure 1 and Table 1.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies indicate that simultaneous targeting of two loci using two pairs of TALENs can induce large genomic deletions [34][35][36][37], inversions as well as chromosomal translocations [38,39]. Using this dual TALEN approach, we and other groups have demonstrated that large deletions of 1-80 kb can be efficiently created in zebrafish [33,[40][41][42]. These large deletions have been used to knock out non-coding RNA genes, gene clusters and gene regulatory elements.…”
Section: Introductionmentioning
confidence: 99%